Education and Anemia Screening in Students of M.H Thamrin Senior High School - Maharani, Eva Ayu; Astuti, Dewi; Lestari, Puji (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Anemia is a condition of reduced number or volume of erythrocytes or hemoglobin (Hb) molecules. This condition can be characterized by a decrease in Hb concentration. Based on data from the Ministry of Health, the prevalence of anemia in teenagers (15-24 years) has increased from 18.4% to 32% from 2013 until 2018. Anemia in teenagers can have an impact on decreasing productivity or academic abilities at school because there is a decrease in student concentration, and they don't feel enthusiasm for learning. This community service activity aims to find out the percentage of students in M.H Thamrin Senior High School who have anemia. The method of community service activities is carried out by examining Hb levels, anemia education, giving blood supplement tablets to students with low Hb levels, and evaluating Hb levels after education and giving the supplement. The results of the examination showed that the Hb levels in 24 female students ranged from 10.1 – 19.2 g/dL, with an average Hb level of 14.5 g/dL. Hb levels in 17 male students ranged from 14.7 – 19.7 g/dL, with an average Hb level of 16.6 g/dL. There were 3 female students (7,3%) who had Hb Levels below the normal value, and 13 students (31,7%) with Hb levels above the normal value. The results of anemia education show an increase in knowledge about anemia among all student participants, with an average score of 72,7 before education and an average score of 96,5 after education. This activity concluded that almost all students had normal Hb levels. However, after being given education and blood supplements and vitamins, two students with low Hb levels have an increase in Hb Levels.